Avaliação do papel de peroxirredoxina 2 na modulação da expressão de outras enzimas antioxidantes em células eritrocitárias K562 - Paula, Carla Peres de (2015)
Reactive oxygen species (ROS) are products naturally generated by the cell metabolism and at low levels play an important physiological role in intracellular regulation, whereas in excess can cause damage to cells. To combat this damage, cells present a complex defense mechanism including different enzymes which act as antioxidants. Among these enzymes, and especially in cells such as erythrocytes, which are exposed to high levels of molecular oxygen, the Peroxiredoxins (Prxs), stand out for the abundance and great reactivity with its substrates. In this cell type, when occurs hemolytic diseases such as sickle cell anemia and beta thalassemia, increased production of ROS and consequently oxidative damage are observed, greatly aggravating the clinical picture of patients affected by these diseases. In these diseases, the PRDX2 appears to be a major line of antioxidant defense, as it is the third most present protein in the cytosol of the erythrocyte. Therefore, this study aimed to assess the role of PRDX2 in differentiated K562 cells for the expression of erythroid characteristics, through gene silencing using shRNA_PRDX2. It was possible to obtain a 70% of the PRDX2 expression inhibition, which caused a decrease in the proliferation, cell viability and interaction, showing the importance of PRDX2 in oxidative protection on this cell type. In order to evaluate the modulation of antioxidant system in these cells, we also analyzed the pattern of gene and protein expression of all other PRDXs beyond the gene expression of other antioxidant enzymes during the process of differentiation. We found that inhibition of PRDX2 expression adversely affects the expression of PRDX5 and causes increased expression of their biological reducing agents, which increase the recycling PRDX2, compensating for their lack the cell. These data are not get described in the literature and additional analysis is needed to better understand this interaction beyond the molecular mechanisms involved in the expression of related enzymes in protection against ROS. Understanding these mechanisms seems important to work with a better insight of the pathophysiology of hemolytic diseases by identifying possible targets to assist in the management and can mitigate the effects of the disease in these patients.